(3MGTjI Ydi GdYOI aj CUhd Gdabgs - (3GdbRhjfj, Ndjd Hf GdZGRj (B, (3J (B1089 (3g`s
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QHH GdYGdejf (B... (3aYdbJ gPg GdMhGTj Ydi cJGH GdYOI aj CUhd Gdabg (B... (3bhdg(B: (3Ef GdTQjYI cdgG eHfjI Ydjgs
(3BNQgG (B:s
(3BNQgG(B: (3aGdJeSc HGdXGgQ ajg jSJdRe LYd GdXGgQ hdjS Ydi Cbhi efg aXGgQ GdHWdGf dCf dg Cf jbhd EfeG GSJOQc Ydi CUd GdMLjI dG Ydi GdbWYjI GjkVGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 321s
(3GdPQjYI, L (B6: 108s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs